2006
DOI: 10.1002/anie.200602431
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Retro‐Cycloaddition Reaction of Pyrrolidinofullerenes

Abstract: Going retro: Controlled‐potential electrolysis (CPE) is employed as a synthetic tool in the selective removal of addends from fullerene adducts. Reductive CPE has been extensively used in the retro‐cyclopropanation of fullerenes without affecting pyrrolidine addends also present. Now oxidative CPE for the selective removal of pyrrolidine addends in the presence of methano adducts is reported (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 24 publications
2
31
1
Order By: Relevance
“…Possibly, the excess C 60 needed for formation of 4 promotes a retro-Prato reaction as the reaction time is extended, as previously reported. 74 The optimal reaction time was found to be 6 h, after which Cu-free rotaxane 4 was isolated in 13% yield after several chromatographic purification steps.…”
Section: Resultsmentioning
confidence: 98%
“…Possibly, the excess C 60 needed for formation of 4 promotes a retro-Prato reaction as the reaction time is extended, as previously reported. 74 The optimal reaction time was found to be 6 h, after which Cu-free rotaxane 4 was isolated in 13% yield after several chromatographic purification steps.…”
Section: Resultsmentioning
confidence: 98%
“…It is worth noting that the second irreversible oxidation process is observed at approximately +1.2 V, which is close to the first oxidation potential of PCBM (+1.24 V versus Fc +/0 ). It has been reported that controlled‐potential electrolysis of fulleropyrrolidines and methanofullerenes at their first oxidation potentials results in retro‐cycloaddition with methano bridge cleavage …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that controlled-potential electrolysis of fulleropyrrolidines and methanofullerenes at their first oxidation potentials results in retrocycloaddition with methano bridge cleavage. [44,45] Double-caged compounds 1a-d demonstrate two irreversible oxidationp eaks at the same positions as fulleroproline esters 2a-d (approximately 1.0 and1 .2 Vv ersusF c + /0 ). Similarly to fulleroproline esters, oxidationi sf ollowed by compound degradation.…”
Section: Electrochemical and Spectroscopic Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…The retro‐cycloaddition process can be also promoted under electrochemical conditions. Thus, controlled potential electrolysis (CPE) for the removal of pyrrolidine moieties from pyrrolidinofullerene derivatives has been reported …”
Section: Methodsmentioning
confidence: 99%